Smoking Induces a Decline in Semen Quality and the Activation of Stress Response Pathways in Sperm - Magda Carvalho Henriques; Joana Santiago; António Patrício; Maria Teresa Herdeiro; Susana Loureiro; Margarida Fardilha (MDPI AG, 2023)
Male infertility is a prevalent concern affecting couples worldwide. While genetic factors, hormonal imbalances, and reproductive system defects play significant roles, emerging evidence suggests that lifestyle choices also profoundly impact male fertility. This study aimed to explore the effects of several lifestyle factors, including tobacco and alcohol consumption, physical activity, and dietary habits, on semen quality parameters and molecular biomarkers. Thirty healthy male volunteers were recruited in the Urology service at Hospital Infante D. Pedro, Aveiro, Portugal. Participants completed lifestyle questionnaires and provided semen samples, which were analyzed according to the World Health Organization criteria by experienced technicians. We also analyzed the expression levels of antioxidant enzymes and heat-shock response-related proteins to explore the activation of signaling pathways involved in stress response within sperm cells. Our results revealed that tobacco consumption reduced semen volume and total sperm count. Although the changes in the percentage of total motility and normal morphology in the smokers' group did not reach statistical significance, a slight decrease was observed. Moreover, we identified for the first time a significant association between tobacco consumption and increased levels of heat shock protein 27 (HSP27) and phosphorylated HSP27 (p-HSP27) in sperm cells, indicating the potential detrimental effects of tobacco on the reproductive system. This study highlights that lifestyle factors reduce semen quality, possibly by inducing stress in sperm, raising awareness about the effects of these risk factors among populations at risk of male infertility.